Cost-effectiveness of on-demand plerixafor added to chemotherapy and granulocyte-colony stimulating factor for peripheral blood stem cell mobilization in multiple myeloma. Issue 1 (2nd January 2018) - Milone, Giuseppe; Martino, Massimo; Leotta, Salvatore; Spadaro, Andrea; Zammit, Valentina; Cupri, Alessandra; Avola, Giuseppe; Camuglia, Maria Grazia; Di Marco, Annalia; Scalzulli, Potito; Morelli, Mara; Olivieri, Attilio; et al.
Abstract: We here report final results of a phase II/III prospective study that evaluated in Multiple Myeloma the use of on-demand plerixafor (PLX) added to mobilizing chemotherapy for patients showing predictive signs of mobilization failure. A total of 111 patients with MM were registered, all received cyclophosphamide 4 g/m 2 and granulocyte colony-stimulating factor (G-CSF). Overall, a successful CD34+ cell mobilization was achieved in 97.2% (108/111) of patients. Minimum harvest (≥2.0 × 10 6 CD34+ cells/kg) was achieved in 97.2% (108/111) and optimal harvest success (≥4.0 × 10 6 CD34+ cells/kg) was achieved in 84.6% (94/111). Multivariate analysis showed that patients who received on-demand PLX treatment had significantly higher likelihoods of successfully achieving both the minimal ( p  = .006) and optimal harvest ( p  = .05) in respect to a historical control group mobilized without any PLX. The incremental cost-effectiveness ratio, for each 1% increase in probability of achieving a successful minimal harvest, was€ 40.6 per patient.